The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/microorganisms11071772
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio in the Gut: The Enemy within?

Abstract: Desulfovibrio (DSV) are sulfate-reducing bacteria (SRB) that are ubiquitously present in the environment and as resident commensal bacteria within the human gastrointestinal tract. Though they are minor residents of the healthy gut, DSV are opportunistic pathobionts that may overgrow in the setting of various intestinal and extra-intestinal diseases. An increasing number of studies have demonstrated a positive correlation between DSV overgrowth (bloom) and various human diseases. While the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 193 publications
0
10
0
Order By: Relevance
“…Independent of these covariates, several gut bacterial genera enriched in individuals with lower BMFs (CORNCOB, p < 0.001), such as Christensenellaceae_R-7_group , Anaerotruncus , Blautia , Family_XIII_AD3011_group (Anaerovoracaceae family), and Methanobrevibacter , were previously found to be enriched in Parkinson’s disease (PD) patients who often suffer from chronic constipation 44 . Desulfovibrio , which has been shown to be enriched in several disease states 45 , was elevated at lower BMF ( Fig. 4 ).…”
Section: Discussionmentioning
confidence: 89%
“…Independent of these covariates, several gut bacterial genera enriched in individuals with lower BMFs (CORNCOB, p < 0.001), such as Christensenellaceae_R-7_group , Anaerotruncus , Blautia , Family_XIII_AD3011_group (Anaerovoracaceae family), and Methanobrevibacter , were previously found to be enriched in Parkinson’s disease (PD) patients who often suffer from chronic constipation 44 . Desulfovibrio , which has been shown to be enriched in several disease states 45 , was elevated at lower BMF ( Fig. 4 ).…”
Section: Discussionmentioning
confidence: 89%
“…Bacteria having the highest SHAP values when using any model with PA were probiotic candidates such as Akkermansia municiphila (Cani et al 2022) and potantially beneficial microbes such as Firmicutes bacterium CAG:95 and Firmicutes bacterium CAG:110 (Zeybel et al 2022). Models using PA as data transformation assigned also higher SHAP values to opportunistic pathobionts such as Desulfovibrio piger (Singh, Carroll-Portillo, and Lin 2023) , Fusobacterium nucleatum (Brennan and Garrett 2019) and Erysipelatoclostridium ramosum (previously known as Clostridium ramosum ) (Bojović et al 2020). This observation further highlights the difference in the biomarker profiles informed by different data transformations.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Odoribacter effectively alleviates colitis in mice through a mechanism that may be related to the regulation of neutrophil extracellular trap formation [ 44 ]. Desulfovibrio is a phylotype related to hydrogen-scavenging and sulfate reduction [ 45 ] and has been implicated in a variety of diseases, but its relationship with IBD remains controversial, and related research results are conflicting [ 46 ]. However, studies have shown that Desulfovibrio may be effective in attenuating liver damage by producing acetic acid and regulating hepatic lipid metabolism in mice [ 47 ].…”
Section: Discussionmentioning
confidence: 99%